China's Belt and Road Initiative (BRI) as a nation branding tool - Mašková, Viktorie (2023)
This Master thesis study Chinese Belt and Road initiative in connection to the nation branding theory. It focuses on the potential use of the initiative in a nation branding strategy by China. The first chapter follow the placement of the nation branding theory in current IR theory with the emphasis on its multidimensionality. The second chapter pursue the topic of the Belt and Road initiative in the context of multidimensional nation branding in a form of a case study. The chapter covers both the BRI’s actions within each dimension, the implications and obstacles it has to face. Last chapter focuses on a comparative case study of two BRI countries: Laos and Malaysia. The aim of this chapter is to discover BRI’s effects on the countries’ perception of China.